Industrial Training Report at Technology Education Division Perak (BTPN Perak) / Aziemah Azhar - Azhar, Aziemah (Universiti Teknologi MARA, Kelantan, 2013)
In the era of globalization, various types of e–learning have been implemented in order to enhance the quality of education. Through the Preliminary Malaysia Education Blueprint 2013 – 2025, the Ministry have invested in a 4G internet access and a virtual learning environment platform that will be provided to all 10 000 schools in Malaysia by 2013. This study assesses the acceptance of Frog VLE, the virtual learning environment system and its relationship with the willingness to assist teachers in implementing the system. It is very important for this study to be conducted in ensuring that the government’s investment towards this learning system is a success. The population of interest for this study is the Technology Education Officers and Computer Technicians who work at Teacher’s Activity Center in Perak. Samples are selected using simple random sampling procedure and 102 of Technology Education Officers and Computer Technicians are selected as sample. This study modifies the questionnaire of Unified Theory of Acceptance and Use of Technology (UTAUT) by Venkatesh, Smith, Morris, Davis and Davis (2003). Structural Equation Modeling is being used to test the hypothesis. The result shows that the facilitating conditions have a significant and direct relationship towards both use behavior and the willingness to assist teachers. On the other hand, system expectancy does not influence both use behavior and the willingness to assist teachers. This study found that use behavior has significantly influence the willingness to assist teachers